2006
DOI: 10.1111/j.1365-246x.2006.03098.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation, uplift and tectonic integration of a Periadriatic intrusive complex (Pohorje, Slovenia) as reflected in magnetic parameters and palaeomagnetic directions

Abstract: S U M M A R YThe Periadriatic lineament is a 700-km-long, first-order tectonic boundary in the Alps, along which several Tertiary intrusions are located that were emplaced while tectonic processes were active. The Pohorje pluton is one of the Periadriatic magmatic suites and comprises a pluton and a dacite stock that were emplaced at depths of about 10 and 2 km, respectively. Oriented samples were collected from 33 sites in the magmatic, and three in the surrounding metamorphic rocks and subjected them to stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The formation is made of granodiorite, which suffered ductile deformation at an estimated temperature of 400 − 450 • C followed by brittle deformation after cooling [19]. This rock has a high susceptibility (≈ 10 −2 SI), extremely high degree of AMS (≈ 35% in average) and lineation (≈ 20% in average) [38]. In this case the classical method by V. Jelinek is a perfect procedure to determine the orientation of the AMS ellipsoid.…”
Section: Field Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation is made of granodiorite, which suffered ductile deformation at an estimated temperature of 400 − 450 • C followed by brittle deformation after cooling [19]. This rock has a high susceptibility (≈ 10 −2 SI), extremely high degree of AMS (≈ 35% in average) and lineation (≈ 20% in average) [38]. In this case the classical method by V. Jelinek is a perfect procedure to determine the orientation of the AMS ellipsoid.…”
Section: Field Examplesmentioning
confidence: 99%
“…In some cases a general trend can be observed that is maintained throughout a stratigraphic sequence, especially in the fine grained clastics (mudstones). This trend can be attributed to weak tectonic deformation [35,14,38,39,40], especially when K3 is close to the bedding pole, i.e. the magnetic foliation is subparallel with the bedding plane.…”
Section: Introductionmentioning
confidence: 99%
“…Since the intensity of natural remanent magnetisation in the tonalites was too weak, drill cores were taken mainly from mafic enclaves present in most of the tonalitic bodies. A similar sampling strategy has been used previously by Márton et al (2006) for the Pohorje pluton at the easternmost end of the PAL.…”
Section: Datamentioning
confidence: 99%
“…One sample (Cezlak granodiorite; SLO; Fig. 2a) originates from the Pohorje complex in N-Slovenia, near Oplotnica (for details see, e.g., Márton et al 2006). The other one is the Flossenbürg granite (FG, Fig.…”
Section: Samplesmentioning
confidence: 99%
“…In the central part of the Pohorje magmatic massive a *40 km long and 7 km wide calc alkaline igneous complex crops out that was emplaced into a polymetamorphic basement (Márton et al 2006). In the SE of this complex a grey granodiorite is quarried, which is characterized by cross cutting of light aplitic and pegmatitic veins of different generations.…”
Section: Cezlak Granodioritementioning
confidence: 99%